HUBUNGAN PENERAPAN PP NOMOR 71 TAHUN 2010 DENGAN AKUNTABILITAS KINERJA LAPORAN KEUANGAN DAERAH PADA SEKRETARIAT DAERAH KOTA BENGKULU - -, Mulyadi; Soleh, Ahmad (Fakultas Ekonomi Universitas Dehasen Bengkulu, 2014)
Mulyadi, Ahmad Soleh;The Relationship between the application of PP No 71 2010 With accountability performance of financial report at regional Secretariat in Bengkulu. This research aims to find out the execution of government regulation Number 71 in 2010. The population in this research is the member of Finance in regional Secretariat Bengkulu. It used census as the sample collection method by choosing 15 person as the sample. The test results show that there is a relationship between the regulation of the Government No. 71 in 2010 with the accountability performance of financial report at regional Secretariat in Bengkulu. while the others is affected by other factors which are not examined by the author. Thus the hypothesis that the authors reveal that PP Number 71 in 2010 affect the accountability performance of financial statements in regional Secretariat in Bengkulu is proved.